2021
DOI: 10.1101/2021.07.22.453350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interaction between a parasite and sub-optimal temperatures contributes to honey bee decline

Abstract: Global insect decline and, in particular, honey bee colony losses are related to multiple stress factors, including landscape deterioration, pollution, parasites and climate change. However, the implications of the interaction among different stress factors for insect health are still poorly understood; in particular, little is known on how challenging environmental conditions can influence the impact of parasites. Here we exploited the honey bee as a model system to approach this problem and carried out exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In conclusion, we confirm that pollen has a beneficial effect on bees challenged with Varroa mite. Varroa infestation at the pupal stage influences the nutritional status of the honey bee ( 23 , 24 ); this compromises the natural maturation by influencing the relationship between two core physiological factors, Vitellogenin and JH ( 27 ). This leads to an accelerated transition to foraging and thus an anticipated death since this transition determines the overall lifespan of the bee ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we confirm that pollen has a beneficial effect on bees challenged with Varroa mite. Varroa infestation at the pupal stage influences the nutritional status of the honey bee ( 23 , 24 ); this compromises the natural maturation by influencing the relationship between two core physiological factors, Vitellogenin and JH ( 27 ). This leads to an accelerated transition to foraging and thus an anticipated death since this transition determines the overall lifespan of the bee ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mite parasitized bees have a lower weight at the emergence, lower protein content and elevated free amino acids levels, suggesting that protein synthesis and growth are disrupted by Varroa ( 23 ). Varroa also influences the food intake of adult honey bees parasitized at the pupal stage (i.e., parasite induced anorexia), likely due to an interaction with the insulin pathway ( 24 ). Varroa can additionally modulate the honey bee's age-dependent behavioral maturation.…”
Section: Introductionmentioning
confidence: 99%
“…This last finding suggests a reduced storage capacity and a reduced immune response in infested bees, mainly due to the lower concentration of vitellogenin, the most abundant protein in honeybee haemolymph, which is also involved in immunity. Accordingly, it has been reported that Varroa infestation affects the nutritional status of honeybees [43,44] and compromises their normal polyethism by altering the interaction between vitellogenin and juvenile hormone, two essential physiological components [45]. In addition, parasitisation reduces the life expectancy and impairs immune system function, increasing the risk of viral infections.…”
Section: Correlations Between Biochemical and Functional Parameters A...mentioning
confidence: 99%
“…In conclusion, we confirm that pollen has a beneficial effect on bees challenged with Varroa mite. Varroa infestation at the pupal stage influences the nutritional status of the honey bee (23,24); this compromises the natural maturation by influencing the relationship between two core physiological factors, Vitellogenin and JH (27). This leads to an accelerated transition to foraging and thus an anticipated death since this transition determines the overall lifespan of the bee (25).…”
Section: Discussionmentioning
confidence: 99%